Proceedings of the XVIII International Conference on Human Computer Interaction 2017
DOI: 10.1145/3123818.3123830
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative learning as educational strategy for deaf children

Abstract: The education of people with disabilities requires special attention and the use of teaching and learning strategies that can be adapted to every particular disability. This study focuses on the education of deaf children as part of a larger project that aims to mix teaching strategies like Logogenia and Fitzgerald Key with interactive storytelling and collaborative learning to support literacy teaching to these children. Since deaf people learn using the visual channel as main input, we believe that technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
5
1
2
Order By: Relevance
“…We used a total of 5 digital libraries, out of these two were not used in the related work, we also had 902 papers identified and 21 papers accepted differently from 229 identified papers and 14 selected, our search string did not contain the word collaborative learning. The results we had differ from that of [Aristizábal et al 2017] paper. We identified age or grade group of the children involved and subjects or topics being taught for each paper.…”
Section: Related Workcontrasting
confidence: 99%
See 1 more Smart Citation
“…We used a total of 5 digital libraries, out of these two were not used in the related work, we also had 902 papers identified and 21 papers accepted differently from 229 identified papers and 14 selected, our search string did not contain the word collaborative learning. The results we had differ from that of [Aristizábal et al 2017] paper. We identified age or grade group of the children involved and subjects or topics being taught for each paper.…”
Section: Related Workcontrasting
confidence: 99%
“…The paper is a systematic literature review based on collaborative learning as an educational strategy for deaf children, collaborative learning in this context is referred to as group learning were students help each other to reach a common goal. [Aristizábal et al 2017] had the objective of identifying how collaborative learning is being applied for educating deaf children and the kinds of technology that has been used in these environments. However, our paper has the goal of describing empirical evidence concerning the positive impacts of technological tools for the education of deaf children.…”
Section: Related Workmentioning
confidence: 99%
“…During thé réviéw of thé litératuré on storytélling [13] and collaborativé léarning (CL) [8] to support litéracy téaching, wé found that théré is a lack of réséarch régarding thé usé of thésé two stratégiés for thé éducation of Déaf childrén. Fortunatély, thé résults of thé studiés that madé usé of any of thésé stratégiés on dévéloping réading and writing skills, show thé éfféctivénéss of using téchnology with oné or both approachés [10] [52].…”
Section: Discussionunclassified
“…In this casé, thé usé of Collaborativé Léarning (CL), a méthod in which studénts work with oné anothér to achiévé a common goal [7], could promoté léarning and communication skills among classmatés. Unfortunatély, théré is not much information about thé usé of CL in thé éducation of Déaf childrén [8].…”
Section: Introductionmentioning
confidence: 99%
“…Deaf education is changing and must not rely on traditional teaching methods; It is moving towards the collaborative learning (Aristizábal et al, 2017), active learning, and deaf-centered curricula that adapt content to suit the capabilities of deaf and HoH students (Skrebneva, 2015). There are a number of different methods that have been applied in some universities for teaching deaf and HoH students.…”
Section: Theoretical Overview: Current Global Realities and Initiatives In Deaf Educationmentioning
confidence: 99%